A review on type of attacks on fingerprint image and watermarking techniques - Lebcir, Mohamed; Suryanti, Awang (IOP Publishing, 2019)
Fingerprint image watermarking techniques have several advantages over traditional security systems that based on token or knowledge. However, they are also vulnerable to attacks that can decrease their security. In this regard, this paper presents a study of a number of research studies on the attacks of fingerprint images watermarking techniques. The attacks can be categorized into intentional and unintentional. We study several attacks based on that category and several fingerprint image watermarking methods. We produce a comprehensive comparison of those methods to show how the methods able to prevent the attacks. We also discuss the advantages and disadvantages of the methods. Therefore, based on that, we can see what are the common attacks on the fingerprint image and what are the methods that efficient in preventing the attacks.